Nilai-Nilai Pendidikan Anak dalam Al-Qur'an: Telaah Tafsir Tematik tentang Pendidikan Anak di Era Digital - Rahmadani Akbar (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The rapid development of technology and globalization in the era of disruption has brought both opportunities and challenges to education, particularly in shaping the moral and spiritual character of the younger generation. Many children and adolescents are vulnerable to negative influences such as materialism, hedonism, and declining social interaction, which highlight the urgent need for educational approaches rooted in strong moral and religious foundations. This study aims to explore the educational values of children in the Qur'an as a solution to forming a generation with noble character in the era of disruption. The research method used is qualitative with a library research approach. The main data sources are relevant verses of the Qur'an, such as QS. Luqman: 13, QS. Al-Isra: 23-24, QS. Adz-Dzariyat: 56, QS. Al-Hujurat: 13, and QS. Al-Alaq: 1-5, as well as interpretations and related literature. The data are analyzed thematically to identify the educational values of faith, morals, worship, social, and intellectual, which are then contextualized with the challenges of the era of disruption. The results of the study show that Qur'anic values, such as monotheism, noble character, and worship, are relevant in forming the character of children who are strong, intellectually intelligent, and spiritually resilient amidst the currents of globalization and technological developments. Strategies for implementing these values include the role of the family, integration into formal education, and strengthening communities based on Qur'anic values. This research makes a significant contribution to the development of Islamic education that can face the challenges of the modern era while maintaining the integrity of religious values.